Alkaloid and iridoid glucosides from Palicourea luxurians (Rubiaceae: Palicoureeae) indicate tryptamine- and tryptophan-iridoid alkaloid formation apart the strictosidine pathway. (May 2020) - Kornpointner, Christoph; Berger, Andreas; Traxler, Florian; Hadžiabdić, Azra; Massar, Magdalena; Matek, Joanna; Brecker, Lothar; Schinnerl, Johann
Abstract: The first phytochemical examination of extracts from leaves and stem bark of Palicourea luxurians (Rusby) Borhidi yielded two undescribed and one known alstrostine derivative together with the oxindole alkaloid javaniside as well as with 5α-carboxystrictosidine. Additionally, five iridoids and four secologanin derived isolation artifacts have been isolated. Lack of strictosidine and its follow-up metabolization products suggested that the Pictet-Spenglerase in P. luxurians does barely or not catalyze the formation of strictosidine. Against this background the biosynthesis of javaniside and 5α-carboxystrictosidine is discussed with regard to possible reaction mechanisms. Similarly, P. luxurians used an independent biosynthetic pathway to produce alstrostine type structures from secologanin and tryptamine in a 2:1 ratio. The structure of isoalstrostine A, which was isolated for the first time, allowed the refinement of a previously reported pathway to the alstrostine type carbon skeleton as well as to some follow-up metabolization products. In spite of various biosynthetic pathways incorporating secologanin to gain different types of tryptophan- and tryptamine-iridoid alkaloids, P. luxurians accumulates this compound as well a couple of further metabolized iridoids deriving from loganin and secologanin. Graphical abstract: Image 1 Highlights: Palicourea luxurians has been phytochemically studied for the first time. Three structural types of tryptophan and tryptamine-iridoid alkaloids were isolated. We report two undescribed alstrostine derivatives. We discuss refinements of the alstrostine biosynthesis. Biosynthesis of javaniside and 5α-carboxystrictosidine is discussed .